2022
DOI: 10.3390/su142013239
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Reality Application for the On-Site Assessment of Building Renovation: Development and Testing

Abstract: This paper contributes to a sustainable construction design management approach to increase the successful renovation rate of existing residential building stock. Indeed, coupling BIM with mixed reality can speed up and improve the quality of the renovation design processes, because it can display virtual models of alternative design scenarios superimposed over the existing physical facility. To this purpose, a sample of technicians was enrolled to test the reliability of this technology. A prototype was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Huang evaluated nine different MR apps for representing architectural design and construction layout 44 . Carbonari used MR to improve the quality of the building renovation design processes 45 . More technically advanced, to teach students indoor illuminance based shading design, Zhao coupled physical illuminance sensors BH1750 and HoloLens to stream and visualize real‐time illuminance values in MR 46 …”
Section: Related Workmentioning
confidence: 99%
“…Huang evaluated nine different MR apps for representing architectural design and construction layout 44 . Carbonari used MR to improve the quality of the building renovation design processes 45 . More technically advanced, to teach students indoor illuminance based shading design, Zhao coupled physical illuminance sensors BH1750 and HoloLens to stream and visualize real‐time illuminance values in MR 46 …”
Section: Related Workmentioning
confidence: 99%
“…Part of the research on Open BIM for infrastructure addresses a certain range of technologies, such as virtual and augmented reality, to improve management procedures and generally develop advanced methodologies. In 2022, Carbonari et al [105] published their paper demonstrating that an MR-based platform can involve interested stakeholders in the assessment of renovation design projects, speeding up the decision-making process and increasing projects' quality. Experimentation in this direction also harks back to earlier work, such as in the case of Zaker and Coloma [106], which involved BIM professionals in order to assess the limitations of applying VR in BIM, and how these issues might be overcome.…”
Section: Vr/ar and Aimentioning
confidence: 99%
“…In the renovation and demolition stage, a total of six articles have been selected with leading research methods such as mixed methods [160][161][162][163][164] and modeling [165], as shown in Table 7. In terms of the number of articles, the renovation and demolition stage is significantly less than the other stages.…”
Section: Renovation and Demolition Stagementioning
confidence: 99%
“…Renovation of building [160][161][162][163]: In the renovation work of buildings, studies focus on achieving effective communication among stakeholders while enhancing designers' perception and understanding of the on-site environment. The BIM4EEB rapid toolkit has been used to develop a DT-based BIM management system that connects to various stakeholders in the AEC domain and provides an interactive multifunctional toolkit [160].…”
mentioning
confidence: 99%
See 1 more Smart Citation